Nutritional Status and Feeding Behavior of Children with Autism Spectrum Disorder in the Middle East and North Africa Region: A Systematic Review - Kittana, Monia; Ahmadani, Asma; Williams, Keith E.; Attlee, Amita (Nutrients, 2023)
Autism spectrum disorder (ASD) in children is associated with increased risks of overweight/obesity and underweight, altered nutrient profile, and abnormal feeding behaviors. This systematic review aimed to elucidate the literature on the nutritional status of children with ASD in the Middle East North Africa (MENA) region, by providing a summary and assessment of the body of evidence. A systematic review of English and Arabic publications up to November 2020 was conducted of five databases in addition to the grey literature, which include a nutrition-related parameter, from both experimental and observational study designs. Children with ASD (ASD-C) between 2 and 19 years in the MENA Region were the target population. For risk of bias, the Academy of Nutrition and Dietetics’ Quality Criteria Checklist (QCC) was adopted. The number of published articles was grossly limited. Forty-three articles were included, of which only four articles reported a low risk of bias; therefore, the results were interpreted in light of methodological limitations. Both overweight and underweight were common in ASD-C, although not consistently different than typically developing children. Nutrient inadequacies of energy, protein, omega-3, and others; deficiencies in serum iron indicators and calcium, as well as vitamins B12, B9, and D levels; and higher levels of homocysteine and omega-6/omega-3 ratios were reported. Feeding behavior problems were also common in ASD-C. Understanding nutritional requirements and food preferences can guide the planning of the appropriate comprehensive interventions for ASD-C. Various nutritional and behavioral concerns were identified in the included studies; however, they were subject to methodological weaknesses, which limited the generalizability of these results. Future research is warranted that must be directed to finding strong evidence using robust study designs on nutritional status and feeding behaviors of ASD-C, with a particular emphasis on the MENA Region.